ANALISIS KINERJA PEGAWAI PADA PT. ASURANSI UMUM BUMIPUTERA MUDA 1967 CABANG BENGKULU - Tito Irwanto; Karona Cahya Susena; Nurhalimah Tusadiyah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
The purpose of this study was to analyze the performance of employees at PT. General Insurance for Young Bumiputera 1967 Bengkulu Branch. This research is a type of survey research that takes a sample from a participant and uses questionnaires as a data collection and participation tool for analysis, explaining and explaining certain phenomena through field research activities. The sample in this study were all employees of PT. 1967 Bengkulu branch of General Insurance Bumiputera Muda who took 18 people with the sampling method used is total sampling or census. The analytical method used in this study is a qualitative descriptive analysis method that uses the average distribution.The results of this study indicate that, the performance of PT. General Insurance for Young Bumiputera 1967 Bengkulu Branch has been very good with an average value of employee performance is 4.24. The average value of work quality is 4.49. The average value of the amount of work is 4.10. The average value of timeliness is 4.14. The average value of cooperation is 4.39. The average value of the cost resolution is 4.20. The average value of supervision is 4.17.Â Keywords: Quality of work, Quantity of work, Timeliness, Cooperation, Emphasis on costs,Â  Supervision